The colorative dark blue in the Old Ukrainian language of the 11th – 13th centuries (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
An investigation of the history of the Ukrainian vocabulary is hardly possible without definition of a formation of separate semantic vocabulary groups, the coloratives in particular. The article deals with the functioning of the colorative dark blue, widely used in ancient texts, and its derivatives in the Old Ukrainian language of the 11th – 13th centuries. The author states unlimited combinations of a nomen dark blue and examines the use of the lexeme both in the literal and metaphorical sense of the word.
Keywords: the name of colour; lexeme dark blue colorative, light blue; dove-coloured; derivative words; abstract lexemes